(untitled) (translation. a transdisciplinary journal, 2022)
What it added to that idea of cultural contact and transformation was of course the relation of power, which maybe had not been so prominent in translation studies i tself, although people like Lawrence Venuti, from a slightly different angle, but in some sense already not entirely foreign to the postcolonial, had been developing i deas about the question of power in translation. So along with that was the role that translation actually performed h istorically as part of the colonial project or whatever you might l ike to call it.